Die Acrolepiidae der China-Ausbeute H. Höne (Lepidoptera: Acrolepiidae). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1971)
In the insects collected by Höne in China and now in the possession of the museum A. Koenig, Bonn, the Acrolepiidae were evaluated. The 15 individuals belonged to six species, four of which, Digitivalva asiatica, D. hoenei, Acrolepiopsis sinense and A. deltoides, were new. Von Acrolepiopsis sibirica (Toll) was first recorded from China.Nomenclatural Actsdeltoides Gaedike, 1971 (Acrolepiopsis), spec. n.sinense Gaedike, 1971 (Acrolepiopsis), spec. n.asiatica Gaedike, 1971 (Digitivalva (Digitivalva)), spec. n.hoenei Gaedike, 1971 (Digitivalva (Digitivalva)), spec. n.